Branched Chain Amino Acids Protects Rat Mesangial Cells from High Glucose by Modulating TGF-β1 and BMP-7 [Corrigendum] - Zhang X; Liu D; He Y; Lou K; Zheng D; Han W (Diabetes, Metabolic Syndrome and Obesity, 2020)
Zhang X, Liu D, He Y, Lou K, Zheng D, Han W. Diabetes Metab Syndr Obes. 2019;12:2433– 2440. The authors of this paper have advised of an error with affiliation 1.Read the original paper here